Perhitungan Biaya Kontruksi Saluran Bermaterial Pasangan Batu Pada Kegiatan Perencanaan Saluran Drainase Jalan di Simpang Seputuk STA 4+400 – 8+600 - Robert, Angelinus; Sulistyani, Kiki Frida; Suhudi, Suhudi (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
An environmentally sound drainage system as a system that is able to keep a facility, especially roads, dry, and can handle problems such as flooding and puddles on the surface, Jalan Simpang Seputuk is an active crossing that is used but there are several obstacles on the left and right side of the road, namely there are puddles of water when it rains, therefore the use of drainage functions is very important. This research uses a quantitative approach method and with secondary data analysis. The study location is topographically in a low and flat position near the Sesayap river which is the downstream of 2 watersheds namely the Seputuk river and the Rian river, the cost budget plan for excavation of soil, soil backfill and left channel stone masonry starts from STA 4+400 - 8+600 Rp2,067,403,777.00. The budget plan for excavation, backfill and right channel pairs starting from STA 4+400 - 8+600 IDR 1,807,281,377.00. With the results of the total cost of planning the drainage channel STA 4 + 400 - 8 + 600 right and left channels IDR 3,874,685,154.00.